Assessment of Microvascular Abnormalities by Nailfold Capillaroscopy in Juvenile Dermatomyositis After Medium‐ to Long‐Term Followup. Issue 5 (23rd March 2018) - Barth, Zoltan; Witczak, Birgit N.; Flatø, Berit; Koller, Akos; Sjaastad, Ivar; Sanner, Helga
Abstract : Objective: In juvenile dermatomyositis (DM), microvascular abnormalities, measured by nailfold capillaroscopy (NFC), are common early in the disease course. We aimed to compare the presence of NFC abnormalities in patients with medium‐ to long‐term juvenile DM with that of controls, and to explore associations between NFC abnormalities and disease activity and other disease characteristics. Methods: Fifty‐eight juvenile DM patients with a median disease duration of 16.8 (range 2–38) years were clinically examined and compared with matched controls. By NFC, we assessed nailfold capillary density (NCD), giant capillaries, scleroderma, and neovascular pattern (defined as scleroderma active or late pattern). NFC was analyzed with researchers blinded to patient/control identity and disease characteristics. We measured disease activity and damage by validated tools, and patients were categorized as having active or inactive disease according to the Paediatric Rheumatology International Trials Organisation criteria. Results: Compared to controls, patients had decreased NCD (mean ± SD 6.4 ± 2.1/mm versus 7.6 ± 0.8/mm; P = 0.001) and showed more abnormality in all other NFC parameters; 36% of patients versus 4% of controls had NCD <6/mm ( P < 0.001). Giant capillaries, scleroderma, and neovascular pattern were found in 9%, 84%, and 41% of patients, respectively. Patients with active disease (n = 30) presented more frequently with neovascular pattern than patients with inactive disease (n = 28) ( P = 0.041). Decreased NCD and neovascular pattern were associated with higher levels of disease activity and impaired muscle function. Conclusion: After medium‐ to long‐term followup, juvenile DM patients had decreased NCD and, often, neovascular pattern; both were associated with higher levels of disease activity and impaired muscle function. This suggests that NFC can be a biomarker for disease activity in longstanding juvenile DM too.